The Use of Extensive Reading Activities to Improve Junior High School Students’ Reading Interest - Nurhanifah, Sitti; Korompot, Chairil Anwar; Fauzan, Muhammad Miftah (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2025)
This study seeks to evaluate the impact of extensive reading on enhancing students' reading interest at SMP Negeri 1 Pallangga. This study utilizes a pre-experimental approach with a one-group pre-test and post-test design, incorporating a questionnaire to assess reading interest. The participants are eighth-grade students from the 2024/2025 academic year, specifically class VIII 5, consisting of 37 students selected through cluster sampling. The instruments used in this study include a reading interest questionnaire with two categories of questions: situational and individual, consisting of 30 questions. The paired samples t-test for the pre- and post-questionnaire yielded a t-value of -17.512, exceeding the t-table value of 2.028, with a two-tailed significance of < 0.001, which is smaller than α = 0.05. This indicates that the null hypothesis (H₀) is rejected, while the alternative hypothesis (H₁) is accepted. In conclusion, extensive reading is proven to be effective in enhancing students' reading interest at SMPN 1 Pallangga.